THE NEED FOR DEVELOPMENT OF SERVICES IN UZBEKISTAN (World Economics and Finance Bulletin, 2022)
The article emphasizes the importance of increasing the volume of services, optimizing its structural structure in the further development of the service sector, and developed scientifically based proposals and recommendations in this regard